TESTING THE LAW OF ONE PRICE - Syratay, Assylzat (Nazarbayev University Graduate School of Business, 2023)
In the realm of international economics, the Law of One Price (LOOP) stands as a foundational concept that underpins our understanding of global trade and market integration. LOOP posits that identical goods should command the same price in different markets, irrespective of geographic boundaries or political jurisdictions (CFI Team, n.d.). Its implications extend beyond economic theory, shaping trade policies and impacting the decisions of businesses and governments worldwide...
Keywords: Type of access: Embargo